Thermal conductivity of calcium silicate boards at high temperatures: an experimental approach - Oliveira, Thiago (2019)
Thermal conductivity analysis of insulation materials is of great importance for determining the critical temperature of structures. The magnitude of this thermal property has a significant influence on the analysis of temperature distribution and heat flow which depends essentially on the thermal properties of the protection material. The most common method for obtaining the required fire resistance is through passive fire protection materials, such as the calcium silicate boards. By using this material, it is possible to slow down the temperature increase on the structural elements surface during a fire situation. Knowing accurate information about the effects of high temperatures on thermal conductivity is certainly an important prerequisite for running a high-performance design involving safety in buildings. Therefore, an investigation of two different calcium silicate boards has been performed to demonstrate how the thermal conductivity is highly affected when exposed to high temperatures. A set of experimental tests is presented. They were conducted in different techniques such as: the transient plane source (TPS) and the guarded hot plate.